Continuing Education of Reference Librarians, 1st edition - Katz, Bill (Routledge, 2020)
This book, first published in 1990, addresses the concerns of librarians that they must be informed and educated in order to excel in their work. It focuses on specific types of training for librarians. Authorities explain pioneering programs in California and Maryland which deal with teaching basic reference tools to beginning librarians and paraprofessionals. They also discuss the role of multitype networks in continuing education as the most cost and time efficient means available today, and the use of self-directed contract learning as a method that requires long-term planning and rewards in contrast to the immediate results of a short-term plan of education. The management perspective of continuing education is also included. Working library directors offer their observations on sound, inspirational approaches to continuing education. They also examine the critical role department heads play as mentor to beginning reference librarians.